2017
DOI: 10.1103/physrevd.95.084004
|View full text |Cite
|
Sign up to set email alerts
|

Counterterm method in Einstein dilaton gravity and the critical behavior of dilaton black holes with a power-Maxwell field

Abstract: We investigate the critical behavior of an (n+1)-dimensional topological dilaton black holes, in an extended phase space in both canonical and grand-canonical ensembles, when the gauge field is in the form of power-Maxwell field. In order to do this we introduce for the first time the counterterms that remove the divergences of the action in dilaton gravity for the solutions with curved boundary. Using the counterterm method, we calculate the conserved quantities and the action and therefore Gibbs free energy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 61 publications
0
23
0
Order By: Relevance
“…In this approach the mass of black hole is treated as the enthalpy [6]. Critical behaviour of black holes in an extended phase space have been explored in various setups [7][8][9][10][11][12][13][14][15]. Recently, this approach has been utilized to present the emergence of superfluid-like phase transition for a class of AdS hairy black hole in Lovelock * Electronic address: asheykhi@shirazu.ac.ir gravity [16].…”
Section: Introductionmentioning
confidence: 99%
“…In this approach the mass of black hole is treated as the enthalpy [6]. Critical behaviour of black holes in an extended phase space have been explored in various setups [7][8][9][10][11][12][13][14][15]. Recently, this approach has been utilized to present the emergence of superfluid-like phase transition for a class of AdS hairy black hole in Lovelock * Electronic address: asheykhi@shirazu.ac.ir gravity [16].…”
Section: Introductionmentioning
confidence: 99%
“…Critical behavior of the Einstein-Maxwell-dilaton black holes has been studied in [28]. When the gauge field is in the form of Born-Infeld [29] and power-Maxwell [30] field, critical behavior of (n + 1)-dimensional dilaton black holes in an extended phase space have been investigated. Taking into account the dilaton field in the presence of logarithmic and exponential forms of nonlinear electrodynamics, and considering the cosmological constant and nonlinear parameter as thermodynamic quantities which can vary, it was shown that indeed there is a complete analogy between the nonlinear dilaton black holes with Van der Waals liquid-gas system [31].…”
Section: Introductionmentioning
confidence: 99%
“…We considered the electrostatic problem of interaction between two point-like charges q 1 and q 2 placed in the points r = ±R by solving the nonlinear Maxwell equation (18), which follows from the least action principle for the Lagrangian (4), together with the standard Bianchi identity (8). For a small separation between the charges, R r , we found the electric field (31) in the approximation, linear with respect to the ratio R/r , which serves as the nonlinear extension of the usual dipole field.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9][10][11][12] and the references therein) with finite selfa e-mail: breev@mail.tsu.ru b e-mail: shabad@lpi.ru energy of the point charge, allied to their famous prototype, the Born-Infeld model [13], where the finiteness of the field is achieved at the cost of square-root nonanalyticity of the Lagrangian, which leads to an infinity to the Maxwell equation. The most popular application [6][7][8][9][10][11][12][14][15][16][17][18][19][20][21][22]] of these models is to combine them with General Relativity in order to study their effect on the initial singularity and on the evolution of the Universe. In contrast to the Born-Infeld model, the models from the class of Ref.…”
Section: Introductionmentioning
confidence: 99%